Bacillus cereus CGMCC 1.60196: a promising bacterial inoculant isolated from biological soil crusts for maize growth enhancement - Zhao, Lina; Kang, Chenrui; Zhang, Shipeng; Cui, Linlin; Xu, Shuaihua; Wang, Yudong; Zhang, Yue; Gu, Shaobin (Frontiers in Microbiology, 2024)
Soil microbial inoculants are widely recognized as an environmentally friendly strategy for promoting crop growth and increasing productivity. However, research on utilizing the microbial resources from desert biological soil crusts to enhance crop growth remains relatively unexplored. In the present work, a bacterial strain designated AC1-8 with high levels of amylase, protease, and cellulase activity was isolated from cyanobacterial crusts of the Tengger Desert and identified as Bacillus cereus (CGMCC 1.60196). The refinement of the fermentation parameters of B. cereus CGMCC 1.60196 determined that the most effective medium for biomass production was composed of 5 g/L glucose, 22 g/L yeast extract and 15 g/L MgSO4, and the optimal culture conditions were pH 6.0, temperature 37°C, inoculation quantity 3% and agitation speed 240 rpm. Furthermore, the utilization of B. cereus CGMCC 1.60196 has resulted in substantial improvements in various growth parameters of maize seedlings, including shoot length, shoot fresh and dry weights, root fresh and dry weights, and the contents of chlorophyll a, chlorophyll b, and total chlorophyll. The most pronounced growth promotion was observed at an application concentration of 1 × 109 CFU/m2. These results suggest that the novel B. cereus strain, isolated from cyanobacterial crusts, can be regarded as an exemplary biological agent for soil improvement, capable of enhancing soil conditions, promoting crop cultivation and supporting food production.